Evaluation of the methodological strategies applied in the english language teaching-learning process to improve pronunciation in the students of first year of bachillerato at zoila ugarte de landívar, santa rosa and dr. Modesto Chávez Franco high schools of bachillerato in Santa Rosa canton, El Oro province, period 2014-2015. - Castillo Herrera, Carlos Geovanny (2015)
The purpose of this research is to determine the level of mastering of pronunciation in the English language, and problems that students of first year of Bachillerato at “Zoila Ugarte de Landívar”, “Santa Rosa” and “Dr. Modesto Chávez Franco” High Schools of Bachillerato in Santa Rosa city, in El Oro province, during the academic period 2014-2015 may have as well as the methodological strategies that teachers apply to improve the before mentioned skill in their students. The gathering of empirical data through interview to the English language teachers, and survey to the students of first year of bachillerato at the above mentioned educational institutions show that there is a high degree of difficulty in the pronunciation skill in the English language by students due to the lack of application of teaching strategies and activities that help them to improve this skill, sometimes for a lack of knowledge or disregard of these strategies by part of teachers, or a lack of interest of their students in the foreign language learning.